Motivating Low-Achievers – Relative Performance Feedback in Primary Schools - Henning Hermes; Martin Huschens; Franz Rothlauf; Daniel Schunk (ZBW - Leibniz Information Centre for Economics, 2020)
Relative performance feedback (RPF) has often been shown to improve effort and performance in the workplace and educational settings. Yet, many studies also document substantial negative effects of RPF, in particular for low-achievers. We study a novel type of RPF designed to overcome these negative effects of RPF on low-achievers by scoring individual performance improvements. With a sample of 400 children, we conduct a class-wise randomized-controlled trial using an e-learning software in regular teaching lessons in primary schools. We demonstrate that this type of RPF significantly increases motivation, effort, and performance in math for low-achieving children, without hurting high-achieving children. Among low-achievers, those receiving more points and moving up in the ranking improved strongest on motivation and math performance. In addition, we document substantial gender differences in response to this type of RPF: improvements in motivation and learning are much stronger for girls. We argue that using this new type of RPF could potentially reduce inequalities, especially in educational settings.
Keywords: I20; I24; C93; 330; relative performance feedback; rankings; randomized-controlled trial; education; gender differences